Vanilla norashikiniana R. Go et A. Raffi sp. nov., a new orchid species from Peninsular Malaysia - Raffi, Akmal; Nordin, Farah Alia; Abdullah, Nur Ashikin Psyquay; Go, Rusea (Malaysian Nature Society, 2017)
A new species, Vanilla norashikiniana R. Go et A. Raffi, from Peninsular Malaysia is described and other aspects of interest discussed. It is so far known from a population in lower dipterocarp forests in Hutan Lipur Chemerong, Hulu Dungun, Terengganu and Hutan Simpan Semangkok, Selangor. A field key to the Peninsular Malaysian taxa (including Vanilla shenzhenica) is also provided.